Long-term effect of 17 beta-estradiol and thrombin on tissue factor pathway inhibitor release from HUVEC - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
In spite of the increasing evidence that estrogens have protective effects on the vascular system, the evidence that estrogens may contribute to the risk of thrombosis is still being debated, We investigated the effect of 17 beta-estradiol (E2) on tissue factor pathway inhibitor (TFPI) release from of cultured human umbilical vein endothelial cells (HUVEC). In this study HUVEC were harvested by collegenase treatment and cultured in multi-welled plates with medium 199 supplemented with 10% fetal calf serum and antibiotics. The cells were incubated in the presence or absence of E2 (1 and 100 nhl) with/without thrombin (4 U/mL) for 6 or 24 hours, After the incubations TFPI level of media were measured by IMUBIND Total Eliza kit. Our results demonstrates that E2 at physiological concentrations decreases the release of TFPI from HUVEC significantly, Thrombin also decreases TFPI antigen levels detected in culture media. When combined with thrombin the effect of estrogen is not visible due the much higher effectivity of thrombin in diminishing TFPI levels. These results show that E2 shifts the hemostatic balance towards the procoagulant phase through lowering the TFPI levels secreted by the endothelium, (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: TFPI; 17 beta-estradiol; thrombin; HUVEC; ORAL-CONTRACEPTIVES; COAGULATION PATHWAY; EXTRINSIC PATHWAY; THROMBOEMBOLIC DISEASE; POSTMENOPAUSAL WOMEN; ENDOTHELIAL-CELLS; ESTROGEN; ACTIVATION; RABBITS; EPI